2012
DOI: 10.1371/journal.pone.0029608
|View full text |Cite
|
Sign up to set email alerts
|

The Organisation of Ebola Virus Reveals a Capacity for Extensive, Modular Polyploidy

Abstract: BackgroundFiloviruses, including Ebola virus, are unusual in being filamentous animal viruses. Structural data on the arrangement, stoichiometry and organisation of the component molecules of filoviruses has until now been lacking, partially due to the need to work under level 4 biological containment. The present study provides unique insights into the structure of this deadly pathogen.Methodology and Principal FindingsWe have investigated the structure of Ebola virus using a combination of cryo-electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
164
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(181 citation statements)
references
References 56 publications
15
164
0
2
Order By: Relevance
“…Polyploidy has also been found in several non-icosahedral virus families (e.g. families Paramyxoviridae, Orthomyxoviridae and Filoviridae), which use it to modulate their virulence (Enami et al, 1991;Rager et al, 2002;Beniac et al, 2012). Therefore, our first objective was to determine whether aquabirnaviruses could also be polyploid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyploidy has also been found in several non-icosahedral virus families (e.g. families Paramyxoviridae, Orthomyxoviridae and Filoviridae), which use it to modulate their virulence (Enami et al, 1991;Rager et al, 2002;Beniac et al, 2012). Therefore, our first objective was to determine whether aquabirnaviruses could also be polyploid.…”
Section: Discussionmentioning
confidence: 99%
“…This fact does not represent a problem for helical viruses such as those mentioned above, as they are more permissive with regard to genome equivalent variations. Furthermore, in the case of filovirus, the particle can modify its length to incorporate up to 22 genome copies (Beniac et al, 2012). However, this fact is not always related to an increase in virulence, as it has been demonstrated that high virulence is sometimes associated with shorter virus filaments (Kiley et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…The viral RNA genome is encapsidated by the NP and together with L, the L cofactor VP35 and the transcriptional activator VP30, as well as VP24, which form a central nucleocapsid in the virus particle. 10 The structure of Ebola virus NP, VP35, VP30 and L are responsible for replication and transcription of viral RNA, while VP40 and VP24 are responsible for assembly, budding and release of virion particles.…”
Section: Structural and Functional Characteristics Of Ebolamentioning
confidence: 99%
“…It should be noted that from the physical viewpoint most of viruses can be considered as nanoparticles, since their linear dimensions are close to 100 nm [12][13][14]. As it is well known, viruses have various shapes, so the spherical shape was chosen as the simplest one to be calculated, and since the shape of such widespread viruses as Human Immunodeficiency Virus (HIV) and Influenza Virus is the same.…”
Section: The Local Field In the Presence Of A Nanoparticlementioning
confidence: 99%